Physicochemical Properties and Water Filtration Performance of Electric Field Fabricated Polyvinylidene Fluoride Membranes - Aneka Firdaus; Agung Mataram; Rahma Dani; Muhammad Satya Putra Gantada; Nukman; Irwin Bizzy; Ahmad Fauzi Ismail (Science and Technology Indonesia, 2026)
This study investigated the use of an electric field-assisted phase inversion method (15 kV) to tailor the properties of PVDF membranes with a thickness of 3 mm. The electric field significantly altered membrane formation, producing porous structures compared to the dense morphology of untreated membranes. Increasing the PVDF concentration (25–35%) reduced the pore size from 11.54 µm to 5.27 µm, resulting in more uniform structures. Surface analysis indicated that the membranes remained relatively smooth, with smaller surface features at higher polymer concentrations. The mechanical properties improved substantially, with the tensile strength increasing from 12.28 MPa to 43.21 MPa and higher stiffness observed. FTIR results revealed enhanced β-phase formation under the electric field, indicating improved chain alignment, supported by increased crystallinity from XRD. In terms of filtration performance, the permeability reached 55.32 L/m2·h·bar, while turbidity rejection exceeded 90% for all treated membranes. These results demonstrate a promising approach for high-performance PVDF membranes and strong potential as composite base materials.